Management Strategies in Advanced Uterine Leiomyosarcoma: Focus on Trabectedin. (18th May 2015) - Amant, Frédéric; Lorusso, Domenica; Mustea, Alexander; Duffaud, Florence; Pautier, Patricia
Abstract : The treatment of advanced uterine leiomyosarcomas (U-LMS) represents a considerable challenge. Radiological diagnosis prior to hysterectomy is difficult, with the diagnosis frequently made postoperatively. Whilst a total abdominal hysterectomy is the cornerstone of management of early disease, the role of routine adjuvant pelvic radiotherapy and adjuvant chemotherapy is less clear, since they may improve local tumor control in high risk patients but are not associated with an overall survival benefit. For recurrent or disseminated U-LMS, cytotoxic chemotherapy remains the mainstay of treatment. There have been few active chemotherapy drugs approved for advanced disease, although newer drugs such as trabectedin with its pleiotropic mechanism of actions represent an important addition to the standard front-line systemic therapy with doxorubicin and ifosfamide. In this review, we outline the therapeutic potential and in particular the emerging evidence-based strategy of therapy with trabectedin in patients with advanced U-LMS.